Conversion of cellulosic materials into nanostructured ceramics - Yih, Victor (Universiti Malaysia Sarawak, UNIMAS, 2009)
Cellulosic materials which include sawdust, wastepaper, corncob and sugarcane bagasse were converted into nanostructured ceramics by submersion in silica colloidal suspension (sol) and followed by the calcination of the cellulosic material/SiO2 composites under controlled conditions. Depending on the conditions used during the calcination process, Carbon/SiO2 composite and nanostructured SiO2 ceramics were obtained. The morphology of resulting nanostructured ceramics and nanocomposites obtained from four types of cellulosic materials were characterized by Scanning Electron Microscopy (SEM), Fourier transformed infrared spectroscopy (FTIR), and CHN analyzer. The effect of cellulosic materials on the properties of nanostructured ceramics and nanocomposites formed were investigated.